Peningkatan Hasil Belajar Siswa Kelas II-A SDN 060913 Medan Tembung melalui Media PANGAN (Papan Perbandingan) - Arianty, Widya; Mushlihuddin, Rahmad; Pohan, Nurmaya (MASALIQ, 2025)
This study is motivated by the low student interest in Mathematics, particularly in the topic of “Comparing Numbers,” which directly affects learning outcomes. The aim of the study is to improve student learning outcomes through the use of concrete learning media called PANGAN (Papan Perbandingan or Comparison Board). This research uses the Classroom Action Research (CAR) method, conducted in two cycles with 17 students as subjects. Data collection techniques included interviews, observation, tests, and documentation. The results show a significant improvement in learning outcomes following the implementation of PANGAN media. In Cycle I, 58.82% of students achieved the Minimum Mastery Criteria (KKM), which increased to 82.35% in Cycle II, surpassing the predetermined success indicator. This improvement indicates that the comparison board is effective in helping students understand the concept of numerical comparison in a concrete and meaningful way. These findings support constructivist theory, which emphasizes the importance of active student engagement in constructing knowledge through direct experience. In conclusion, the use of concrete learning media such as PANGAN plays a vital role in enhancing student learning outcomes. The implications include contributions to the literature on concrete instructional media and practical recommendations for teachers in selecting strategies that foster student interest and comprehension. This study also opens opportunities for further exploration of other concrete media in the context of elementary mathematics education.